2018
DOI: 10.5815/ijmecs.2018.10.04
|View full text |Cite
|
Sign up to set email alerts
|

Framework for Software Code Reviews and Inspections in a Classroom Environment

Abstract: Code reviews and inspections have the purpose to ensure that the code has sufficient quality to be released. It is generally seen as an economical way of finding errors, increase team productivity and sharing technical and product knowledge among team members. This approach is traditionally adopted in software development companies, but their practices may be useful in other contexts, such as in the process of learning software engineering. In this sense, this study proposes an innovative framework for conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Only a few studies have reported about using code review in computer science courses [1,22,23]. However, the findings suggest that using code reviews by students increases their self-confidence and that the benefits gained in the classroom are similar to the benefits found in production.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Only a few studies have reported about using code review in computer science courses [1,22,23]. However, the findings suggest that using code reviews by students increases their self-confidence and that the benefits gained in the classroom are similar to the benefits found in production.…”
Section: Related Workmentioning
confidence: 97%
“…Digital Object Identifier (DOI): 10.24138/jcomss-2021-0046 quality of corresponding developing process. One of the most examined methods of refining a program quality is using code review [1]. A modern code review, frequently used in practice these days, is informal, tool-based, and asynchronous [2].…”
Section: Introductionmentioning
confidence: 99%